Analiza Schematów Statycznych Konstrukcji Drewnianych - Wierzbicki, Witold (Engineering Transactions, 1955)
The computation of redundant quantities in timber structures and the determination of critical forces in timber struts are based on Hooke’s law. It is necessary, however, to take into consideration, at the same time, the special conditions for timber structures, as well as the hetero-geneity and the anisotropy of wood. The methods of statical computation of timber structures differ therefore from those for other materials. This paper is concerned with the analysis of the three most typical elements for timber structures. These are: non-prismatic struts, built-up girders and brace structures. The analysis results in the determination of a number of structural properties of those systems. Sec. II contains a description of a calculation method of conical timber struts, in particular pit-props. In Sec. III a conclusion is reached that upper beams of built-up girders should be made of better material than the lower ones. In Sec. IV the degree of exactness is determined, for which the beams of brace systems can be treated as composed of segments, for the determination of bending moments, and as continuous beams, for the determination of the reactions.